Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/mi12010096
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Three-Dimensional Multicellular Spheroid Culture and Future Development

Abstract: Three-dimensional multicellular spheroids (MCSs) have received extensive attention in the field of biomedicine due to their ability to simulate the structure and function of tissues in vivo more accurately than traditional in vitro two-dimensional models and to simulate cell–cell and cell extracellular matrix (ECM) interactions. It has become an important in vitro three-dimensional model for tumor research, high-throughput drug screening, tissue engineering, and basic biology research. In the review, we first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 117 publications
1
49
0
Order By: Relevance
“…In this sense, migration assays using A431 spheroids showed that CAF-derived CM could also promote EMT, since increased explant expansion was observed from A431 spheroids treated with CAF-derived CM in combination with PDT compared to PDT alone. This results are in line with existing literature [ 44 ] and a deeper characterization of this aspect will need to be addressed in future studies. Overall, these data broaden the implications of our findings, as the use of multicellular spheroids is a powerful tool that more accurately mimics the in vivo events.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this sense, migration assays using A431 spheroids showed that CAF-derived CM could also promote EMT, since increased explant expansion was observed from A431 spheroids treated with CAF-derived CM in combination with PDT compared to PDT alone. This results are in line with existing literature [ 44 ] and a deeper characterization of this aspect will need to be addressed in future studies. Overall, these data broaden the implications of our findings, as the use of multicellular spheroids is a powerful tool that more accurately mimics the in vivo events.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, the reduced basal ROS levels found in SCC13 cells may contribute to the intrinsic relative resistance to PDT displayed by this cell line and limit the susceptibility to develop increased resistance to PDT in response to exogenous TGFβ1. Accordingly, some authors have evidenced that higher secretion levels of endogenous TGFβ1 can reduce the sensitivity to exogenous TGFβ1, probably due to the saturation of the pathway by the autocrine signalling [ 44 , 48 , 49 ]. Hence, the high secretion levels of TGFβ1 found in SCC13 cells could further explain the lack of resistance to PDT observed in this cell line in the presence of TGFβ1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-High production costs. [11,25,28,47,98,[106][107][108][109][110][111][112][113][114][115][116][117][118][119] Using acoustic assembly, only a few seconds are needed to obtain simple geometry of microgel units. In addition to this, cell viability can also be highly maintained through this method.…”
Section: Acoustic Assemblymentioning
confidence: 99%
“…With the help of these unique fluid phenomena, microfluidic can achieve a series of micromachining and micromanipulation. Now, microfluidic is considered to have great development potential and wide application prospects in biomedical research [25,98,[109][110][111][112]. With respect to in vitro bionics, microfluidic chips are very suitable for realizing physiological functions at the level of tissues and organs in vitro by using biomaterials such as bionic microstructures and hydrogels, which are also called "organ-on-chips" [113][114][115].…”
Section: Microfluidic-based Assemblymentioning
confidence: 99%